A Nationwide Multicenter Study on 1-Year Outcomes of Posterior Chamber Phakic Intraocular Lens Implantation for Low Myopia - Kamiya, Kazutaka; Shimizu, Kimiya; Igarashi, Akihito; Kitazawa, Yoshihiro; Kojima, Takashi; Nakamura, Tomoaki; Ichikawa, Kazuo; Fukuoka, Sachiko; Fujimoto, Kahoko; , The Japan ICL Study Group (Frontiers in Medicine, 2022)
Purpose To assess the nationwide multicenter outcomes of posterior chamber phakic intraocular lens implantation with a central hole (EVO-ICL, STAAR Surgical) for patients with low myopia. Methods This multicenter study comprised 172 eyes of 111 consecutive patients undergoing hole ICL implantation to correct low myopia and myopic astigmatism [manifest spherical equivalent (MSE);−3 diopters (D) or less] at seven nationwide major surgical facilities. We retrospectively determined safety, efficacy, predictability, stability, and adverse events at 1 week, 1, 3, 6, and 12 months postoperatively, and at the final visit. Results The mean follow-up period was 1.4 ± 1.0 years. Uncorrected and corrected visual acuities at 1 year postoperatively were −0.17 ± 0.12 and −0.24 ± 0.07 logarithm of the minimal angle of resolution (logMAR), respectively. At 1 year postoperatively, 91% and 100% of eyes were within 0.5 and 1.0 D of the target correction, respectively. No significant manifest refraction changes of −0.07 ± 0.26 D occurred from 1 week to 1 year. No vision-threatening complications occurred at any time in this series. Conclusions According to our experience, the EVO-ICL performed well without significant complications throughout the 1-year observation period, even for the correction of low myopia. It is suggested that current ICL implantation is one of the viable surgical options for correcting low myopia.